Risk issue adoption in an online social movement field. Issue 13 (9th November 2020) - O'Neil, Mathieu; Ackland, Robert
ABSTRACT: This article extends the field conceptualisation of social change and innovation adoption, which hinges upon the strategic capacities of actors, to the online environment. We focus on a key aspect of social movement organisations (SMOs), competition for members, resources and attention over an environmental risk issue. The incorporation of network theory enables us to map how the structural position of actors in the field is associated with their actions – for example, their response to an exogenous shock such as a new threat to the environment. We analyse how actors in the online environmental movement respond to the emergence of nanoscience and technology (NST) as a risk issue, and test the field theory hypothesis that dominated actors are more likely to adopt this issue in the early stages of emergence. Our findings challenge field theory orthodoxy and suggest that whilst challengers innovate, dominants co-opt by adopting the issue in a second stage. Finally, we examine why the notion that NST entails significant environmental and health risks was not propelled into wider public consciousness.